Klasifikasi Penyakit Jantung dengan Menggunakan Algoritma C4.5 - Arni Sepharni; Iwansyah Edo Hendrawan; Chaerur Rozikin (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
Heart disease is one of dangerous diseases. The late treatment for the disease will endanger the life of the sufferers. This problem is caused by the difficulty of early detection in patients with heart disease because they always ignore the initial symptoms. In addition, the costs involved in examining heart disease are not cheap because it requires examinations carried out by specialists and laboratory tests. The prediction system is one of options that can be used to perform early detection of heart disease patients at a lower cost, with the costs used in examinations by specialist doctors and laboratory tests can be eliminated and replaced by a prediction system. This study aims to create a prediction system using the C4.5 algorithm by which the predictions based on historical data of the patient to be examined are made. The results obtained from using the C4.5 algorithm to make predictions show an accuracy of 79%, meaning that the results can be expected to be a source of information for further research on prediction systems using the C4.5 algorithm.